2022
DOI: 10.31223/x5s92d
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A very unconventional hydrocarbon play: the Mesoproterozoic Velkerri Formation of Northern Australia

Abstract: The ca. 1.5–1.3 Ga Roper Group of the greater McArthur Basin is a component of one of the most extensive Precambrian hydrocarbon-bearing basins preserved in the geological record, recently assessed as containing 429 million barrels of oil and eight trillion cubic feet of gas (in place). It was deposited in an intra-cratonic sea, referred to here as the McArthur-Yanliao Gulf.The Velkerri Formation forms the major deep-water facies of the Roper Group. Trace metal redox proxies from this formation indicate that i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The Palaeoproterozoic–Mesoproterozoic McArthur Basin in northern Australia has been the subject of considerable study into syn‐depositional basin processes and conditions, from which a confident understanding of the prolonged sedimentary system is emerging (see Cox et al, 2022, for an overview). Overlying Palaeoproterozoic basement of the North Australian Craton, the McArthur Basin is an unmetamorphosed and largely undeformed sequence of sedimentary and volcanic rocks deposited over a period of more than 500 million years (e.g., Ahmad & Munson, 2013; Rawlings, 1999; Yang, Collins, Blades, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The Palaeoproterozoic–Mesoproterozoic McArthur Basin in northern Australia has been the subject of considerable study into syn‐depositional basin processes and conditions, from which a confident understanding of the prolonged sedimentary system is emerging (see Cox et al, 2022, for an overview). Overlying Palaeoproterozoic basement of the North Australian Craton, the McArthur Basin is an unmetamorphosed and largely undeformed sequence of sedimentary and volcanic rocks deposited over a period of more than 500 million years (e.g., Ahmad & Munson, 2013; Rawlings, 1999; Yang, Collins, Blades, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Lithologically, the Roper Group comprises of a series of coarsening-up sequences dominated by marine mudstone and interbedded sandstone with minor successions of intraclastic limestone (Abbott and Sweet, 2000;Ahmad and Munson, 2013;Jackson et al, 1987; 130 Yang et al, 2018). Records of water-column euxinia and redox stratification as well as fluctuating salinity levels suggests that the Roper Group formed in an intermittently restricted marine basin within an epicontinental setting similar to the modern Black Sea, or Baltic Sea (Ahmad and Munson, 2013;Beyer et al, 2016;Cox et al, 2022;Cox et al, 2016;Mukherjee and Large, 2016;Revie and MacDonald, 2017;Yang et al, 2018).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…In this study, we show how in situ Rb-Sr analysis of the Proterozoic Velkerri Formation in the Roper Group, McArthur Basin, northern Australia (Figure 1) dated clay-mineral recrystallisation at temperatures similar to those at 100 which kerogen catagenesis occurs. The Roper Group is a good case study for in situ Rb-Sr shale dating as it has been shown to be dominated by authigenic clays (Rafiei and Kennedy, 2019;Subarkah et al, 2021) and is chronologically well-constrained (Ahmad and Munson, 2013;Bodorkos et al, 2020;Cox et al, 2022;Kendall et al, 2009;Southgate et al, 2000;Subarkah et al, 2021;. Furthermore, the resurgence of interest in the resource potential of the organic-rich Velkerri Formation has also yielded a framework of palaeotemperature data 105 that aim to discern the maturation history of hydrocarbons within the unit (Ahmad and Munson, 2013;Capogreco, 2017;Cox et al, 2016;Crick et al, 1988;George and Ahmed, 2002;Jarrett et al, 2019;Lemiux, 2011;Revie, 2014;Summons et al, 1994;Taylor et al, 1994;Volk et al, 2005).…”
mentioning
confidence: 99%
See 2 more Smart Citations